Development Of Microwave Bandpass Filter Using Defected Ground Structure In Comparison With Multilayer And Dielectric Resonator Filters - Sulaiman, Ahmad Asari (2012)
Bandpass filters perform an important filtering task in a radio transceiver. The narrow stopbands and low gradient in transition bands of conventional parallel-coupled or electromagnetic band gap (EBG) are two (2) of the challenges in designing a bandpass filter. This thesis will introduce three (3) structures of bandpass filter. The first is a new combination of parallel-coupled and defected ground structure (DGS) that operates at a center frequency of 7.8 GHz for mobile satellite application. In essence, this combination structure has resulted to high Q-factor and slow wave which contributes to a high slope and spurious suppression. Cylindrical dielectric resonators were also applied to the circuit in order to increase the return loss in the passband or to enhance the bandwidth of the design. The Zirconate Tin Titanate, ZrSnTiO3 (  r = 37.4, tangent loss = 0.002) dielectric resonator and RO3003 substrate with dielectric constant and tangent loss of 3.0 and 0.0013 respectively were applied in this project. The overall dimension of the circuit was 47.2 mm × 19.16 mm, while the size of the rectangular DGS was 1 mm × 7.36 mm. The second structure is a combination of end-coupled and split ring resonators in a multilayer configuration that operate at 3.47 - 3.79 GHz for Worldwide Interoperability for Microwave Access (WiMAX) application. A modified split ring was introduced to obtain the additional sub-resonators from the magnetic coupled between vertical layers in order to increase the coupling effect from the multilayer structure. The Flame Retardant 4 (FR-4) substrate with dielectric constant, r of 4.6 was used as a core material.